(untitled) (European Journal of Health Research, 2020)
Is an increasingly frequent pathology in our society due to the general increase in life expectancy. It has a extensive social and economic impact. An epidemiological study is essential to describe the predominant characteristics of the patients affected by such fractures that help us adopt the most convenient and individualized treatment in each case. Usually, these types of patients have abundant associated pathologies that condition the prognosis in the short and long term. The etiology is multiple, there are clear predisposing factors such as osteoporosis, constitutional factors (age, race), nutritional status, weight, toxic habits, intake of medications, etc. Elderly people may even be depleted from doing their usual activities and personal hygiene. Hip fracture is common among women due to osteoporosis. They are classified according to the type of fracture and the anatomical location. The initial diagnosis is made by physical examination and the use of radiographs. Early surgical treatment has been shown to improve functional results and decrease mortality. Its objective is to repair or replace the fractured bone. There is a need to create specialized multidisciplinary care that is capable of identifying and treating specific requirements.